Analisis rencana strategis pemerintah kabupaten banyuwangi dalam penanggulangan bencana alam - Burhanudin Mukhamad Faturahman (Publisia: Jurnal Ilmu Administrasi Publik, 2020)
Strategic plan is  series of stages rational thought to produce an effective strategy. The purpose to know strategy of Banyuwangi Regency Government in response natural disasters through strategic plan (Renstra). Research Methods use qualitative descriptive approach and data analysis use content analysis to analyze document of regional disaster Management Agency (BPBD) Banyuwangi Regency Year 2019-2021 use Vision of Success Approach from Bryson. The results show that the vision of the National Medium-Term Development is used as a reference for Banyuwangi Regency BPBD Strategic Plan in dealing with natural disasters at local level. This is also supported by the vision of selected regional heads who are committed to providing public services including disaster services on aspects of natural disaster risk reduction and optimization of natural disaster emergency response management. In addition, strategies to manage disaster issues are optimizing organizational management and strengthening the tasks and functions of disaster management comprehensively. However, the process of strategic planning stages there is still no systematic schedule and communication still relies on disaster information from the Meteorology and Geophysics Agency. BPBD Strategic Plan is local governments guideline to take disaster policies so that the documents compiled by BPBD must be complete and comprehensive. DOI: 10.26905/pjiap.v5i1.3607